A socio-legal approach to the abandonment of infants in Cape Town. - Luther, Susanna (Department of Public Law, 2025)
This dissertation considers the impact of the law in its current form on service providers for abandoned infants in Cape Town. It looks at what works, what does not, and possible solutions. The topic is examined through qualitative empirical research in Cape Town with social workers who work with abandoned infants. A thematic content analysis of the data collected from six interviews shows that the system is failing infants abandoned in Cape Town. The social workers suggested that possible solutions include safe haven laws, baby savers, education, and publicity.